Penerapan Pola Relief Meander Dalam Konservasi Kebudayaan Pembuatan Batik Cap Khas Desa Ngawonggo Kecamatan Tajinan - Mustika, Ulfa Dyah; Sujiantoro, Hibertus; Refangga, Galih Setyo; Lestari, Dinna Eka Graha; Khoirunnisa, Iffa; Lentari, Resita Arum (STIE Malangkucecwara, 2024)
Ngawonggo Village located in Tajinan District, Malang Regency has a great potential in the field of culture with the existence of the Patirtaan Ngawonggo Site, the village community participates in the preservation of this historical site, in the development of the Partirtaan Ngawonggo Site, the method used is in the form of training with introduction and direct practice about batik stamp Patirtaan Ngawonggo Site. The result of this activity is that Wisnuwardhana University Malang made the latest ideas without changing its traditional concept in the form of education and development of UMKM by providing workshops on making Cap Khas Ngawonggo Batik whose motifs were inspired by the pattern of application of meander motifs and combined with tendrils on the walls of the Patirtaan Ngawonggo Site statue. The meander motif symbolizes the bond of continuous life between man and nature